2013
DOI: 10.5658/wood.2013.41.5.440
|View full text |Cite
|
Sign up to set email alerts
|

Change of Heating Value, pH and FT-IR Spectra of Charcoal at Different Carbonization Temperatures

Abstract: To understand transition characteristics from wood to charcoal, Quercus variabilis wood was carbonized at 200, 250, 300, 340, 540 and 740°C, respectively. Heating value, pH and surface property by FT-IR spectroscopy of the carbonized charcoal were investigated. Heating value and pH increased with increasing carbonization temperature from 4500 cal/g and 4.3 of the control wood to 8,000 cal/g and 9 of the charcoal carbonized at 740°C, respectively. From FT-IR spectroscopy, the peaks from O-H, C-H and CO stretchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…5a and b show that the underlying chemical structure of the firewood species and charcoal produced by slow pyrolysis of these species is very similar as spectrograms do not show significant differences as the tree species used for producing charcoal are the same firewood species. Different studies have also shown similar spectra for firewood species and charcoal [23,58]. Bands observed between 3900 and 3500 cm −1 are associated with O − H vibrations in hydroxyl groups due to the presence of phenolic groups [59].…”
Section: Ftir Analysismentioning
confidence: 59%
“…5a and b show that the underlying chemical structure of the firewood species and charcoal produced by slow pyrolysis of these species is very similar as spectrograms do not show significant differences as the tree species used for producing charcoal are the same firewood species. Different studies have also shown similar spectra for firewood species and charcoal [23,58]. Bands observed between 3900 and 3500 cm −1 are associated with O − H vibrations in hydroxyl groups due to the presence of phenolic groups [59].…”
Section: Ftir Analysismentioning
confidence: 59%
“…5) in NIR spectra resulted in a diverse range of degradation parameters [16]. Kwon et al [41] commented that chemical and physical characteristics of wood components in cell walls can be easily changed by increasing carbonization temperature. Also, Davrieux et al [12] separated charcoal samples of Tabebuia serratifolia from Eucalyptus grandis by applying PCA and discriminant factorial analysis with NIR spectra in raw form.…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…The pH values ranged from 9.45 to 9.77, which were slightly higher than the charcoal produced from the traditional kiln (Table 3). Kwon et al (2012Kwon et al ( , 2013 reported that the pH values of charcoal prepared from oak wood increased with increasing carbonization temperature, changing from acidic to basic. The pH change might be due to differences in the type and quantities of acidic and basic functional groups, such as carboxylic acid, carboxylic anhydride, lactone, lactol, and pyrone (Boehm 1994(Boehm , 2002.…”
Section: Comparison Of Physical Characteristics and Proximate Analysis Of Charcoal Produced Over One Year From Thermal Therapy Kilnsmentioning
confidence: 99%